TANGGUNG JAWAB SOSIAL PERUSAHAAN SUATU KAJIAN KOMPREHENSIF - Hartono, Sri Redjeki (Jurnal Legislasi Indonesia, 2009)
Corporation has a great influence as a part of the society, forthat reason only, the existence of a corporation will alwaysbe apparent in the society. Corporation has a dual function inthe society, first it will supply the society with primary,secondary and tertiary needs, secondly corporation has thefunction as the employment agent, because the corporationneeds workers to maintain their operations. To fulfill thesociety’s need, corporation exploit both nature and people,that exploitation could be harmful and created positive andnegative impact toward nature and people. To protect bothnature and people from those impacts, a set of legal ruleshould be created in order to force corporations to developedcorporate social responsibility practice into themselves. Tatcorporate responsibility is moving from mere a moralresponsibility into legal responsibility.